English as a third language in Norwegian schools. A study on English teachers' multilingual competence and knowledge of third language acquisition - Pedersen, Line (UiT Norges arktiske universitet, 2016)
This study investigates whether or not English teachers have the ability to teach English as an L3. The basis of this is the increase in multilingual pupils in Norwegian schools that are acquiring/will be acquiring English as their third language. The research question is as follows: ”Do English teachers have sufficient knowledge and competence in multilingualism to teach English as a third language to multilingual pupils?” As well as answering the research question, the study seeks to answer a hypothesis that involves the teacher training programs in Norway, as it is during these programs that English teachers prepare and develop the necessary knowledge to teach the English subject. The hypothesis reads: ”Teacher training programs in Norway do not provide English teachers with the necessary multilingual competence to teach English as an L3”. On the basis of the research question, a quantitative approach in form of a questionnaire is used to gain the necessary information about the respondents’ awareness and knowledge about the phenomenon that is multilingualism. The questionnaire was conducted in the Tromsø area, and there were a total of 8 English teachers that participated in the study. Some of them have prior experience with working with multilingual pupils and some that don’t. The results of the questionnaire indicate that English teachers lack sufficient multilingual competence to teach English as a third language, as they are not fully aware of the complexity that comes with third language acquisition. The results also indicate that teacher training programs don’t have the necessary focus on multilingualism and third language acquisition that they should have.